Silver and Yttrium-Doped Silver Nanoparticles From Pine Needle Leaf Extract: Synthesis, Characterization, Antioxidant, Antiuropathogenic Bacterial, and Docking Activities - Nourhane A. Darwich; Malak Mezher; Alaa M. Abdallah; Zeinab Hachem; Ahmed F. El-Sayed; Rana El Hajj; Taymour A. Hamdalla; Mahmoud I. Khalil (Bioinorganic Chemistry and Applications)
To treat urinary tract infections (UTIs), biosynthesized silver and yttrium-doped silver nanoparticles (AgNPs and Y-AgNPs) were synthesized from pine needle leaf extract (PNLE). The crystalline nature of the NPs was demonstrated by X-ray diffraction. Transmission and scanning electron microscopy showed that AgNPs and Y-AgNPs are dispersed and spherical, with average particle sizes of 18.43 and 26.58 nm, respectively. The chemical composition and oxidation states were revealed by X-ray photoelectron spectroscopy, while the elemental compositions were explored by energy-dispersive X-ray analysis. The functional groups and absorbance peaks were revealed by Fourier transform infrared spectroscopy and ultraviolet-visible spectroscopy, respectively. The NPs possessed luminescent behavior based on photoluminescence studies and ferromagnetic behavior according to vibrating sample magnetometer analysis. In addition, antibacterial activity against six uropathogenic bacteria was assessed by performing microdilution assays to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) which ranged between 0.0625 and 2 mg/mL, agar well diffusion assay with zones of inhibition 8–17 mm, time-kill test detecting inhibition after 3 h, and antibiofilm screening assays at concentrations ranging between 0.0625 and 1 mg/mL. The antioxidant activity was determined by the 1,1, diphenyl 1-2 picrylhydrazyl (DPPH) radical scavenging assay, which showed a significant antioxidant activity (14.2%–55.6%). Docking studies showed that AgNPs and Y-AgNPs can inhibit the vital enzymes DNA gyrase, penicillin-binding proteins, carbapenemase, LasR-binding protein, and dihydropteroate synthase. These results highlight the use of AgNPs and Y-AgNPs as alternative approaches in the battle against antibiotic-resistant UTIs. The research illustrates the increased bioactivity of Y-AgNPs compared with conventional AgNPs. It paves the way for the use of novel nanomaterials in antimicrobial medicine.